1996
DOI: 10.1161/01.cir.93.8.1542
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal Thickening After Severe Coronary Artery Injury Is Limited by Short-term Administration of a Factor Xa Inhibitor

Abstract: The specific factor Xa inhibitor rTAP, when given in fully anticoagulant doses for a short duration after coronary artery injury in the porcine model, resulted in a long-term decrease in neointimal thickness. These results implicate thrombin generation in neointimal formation and suggest that administration of a potent antithrombotic for several days immediately after the procedure may influence the long-term outcome of the coronary injury with a decrease in neointimal formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 38 publications
2
28
0
1
Order By: Relevance
“…This may account for our previous observation of attenuated neointimal thickening and luminal stenosis in minipigs subjected to similar carotid injury procedures and rTFPI infusions. 15 It is also consistent with data from other experimental studies showing inhibition of neointimal thickening after either direct inhibition of thrombin 6 -8,28 or its generation from tissue factor/factor VIIa 15,29 or Xa 30,31 and with clinical evidence of reduced restenosis in patients treated with antibodies to platelet glycoprotein IIb/IIIa receptors after angioplasty, 32 which appears to inhibit thrombin generation both by decreasing the number of platelets in thrombi that support assembly of prothrombinase and by interfering with platelet activation. 33 Despite variability in the accumulation of radiolabeled platelets and fibrin(ogen) among control animals, it is apparent that both rTFPI and heparin reduced the net accumulation of thrombus over time (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…This may account for our previous observation of attenuated neointimal thickening and luminal stenosis in minipigs subjected to similar carotid injury procedures and rTFPI infusions. 15 It is also consistent with data from other experimental studies showing inhibition of neointimal thickening after either direct inhibition of thrombin 6 -8,28 or its generation from tissue factor/factor VIIa 15,29 or Xa 30,31 and with clinical evidence of reduced restenosis in patients treated with antibodies to platelet glycoprotein IIb/IIIa receptors after angioplasty, 32 which appears to inhibit thrombin generation both by decreasing the number of platelets in thrombi that support assembly of prothrombinase and by interfering with platelet activation. 33 Despite variability in the accumulation of radiolabeled platelets and fibrin(ogen) among control animals, it is apparent that both rTFPI and heparin reduced the net accumulation of thrombus over time (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…40 However, because direct thrombin inhibition induces only transient attenuation of bound-thrombin activity, 19 inhibition of the tissue factor pathway or the Xa/Va complex may be a more effective strategy for inhibiting neointimal hyperplasia after arterial injury. [41][42][43][44] Our findings are consistent with clinical observations of persistent prothrombin activation in patients with thrombotic complications of coronary artery disease that is not inhibited by heparin or direct thrombin inhibitors. 38,[45][46][47] The persistence of Xa/Va activity after arterial injury also likely contributes to the increases in thrombin activity that occur after discontinuation of thrombin inhibitors or heparin.…”
Section: Significance Of Procoagulant Activity Bound To the Arterial supporting
confidence: 88%
“…The authors found a trend toward reduced cross-sectional narrowing. The effectiveness of a prolonged inhibition of antithrombotic activity was initially suggested by Schwartz et al 31 in the pig model after metallic stent implantation. The authors demonstrated a decrease in neointimal thickening in coronary arteries after administration of TAP for 5 days.…”
Section: Discussionmentioning
confidence: 95%